2018
DOI: 10.1155/2018/6561901
|View full text |Cite
|
Sign up to set email alerts
|

A Novel and Inexpensive Approach for Force Sensing Based on FSR Piezocapacitance Aimed at Hysteresis Error Reduction

Abstract: Force-sensing resistors (FSRs) are inexpensive alternatives to load cells. They are suitable for applications where noninvasive devices are needed to measure force, stress, or pressure. However, they have been proved to be hysteresis prone and offer nonrepeatable readings due to their highly voltage-dependent electrical resistance. A piezocapacitive effect has been found as an alternative phenomenon that is able to offer force-dependent readings of capacitance with less hysteresis error. Also, this capacitance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 35 publications
2
10
0
Order By: Relevance
“…The same conclusion can be stated for the other voltage intervals of Equations (5) and (6). Concerning the hysteresis error, a similar demonstration to Equation (10) has been presented by the authors in Reference [22].…”
Section: Error Sources and Types Of Error In Fsrssupporting
confidence: 78%
See 3 more Smart Citations
“…The same conclusion can be stated for the other voltage intervals of Equations (5) and (6). Concerning the hysteresis error, a similar demonstration to Equation (10) has been presented by the authors in Reference [22].…”
Section: Error Sources and Types Of Error In Fsrssupporting
confidence: 78%
“…Considerable reduction in the hysteresis error is also reported in Figure 8. Nonetheless, this is not surprising since previous authors' work has demonstrated that CFSR measurements yield lower drift and hysteresis errors [21,22]. This statement is also supported by the inequality of Equation (10).…”
Section: Trimming the Offset Resistances For R 1 = Rsupporting
confidence: 62%
See 2 more Smart Citations
“…Metal rubber is made by twisting wire into a spiral coil, winding the spiral coil according to a certain process, and finally cold stamping it [3]. Metal rubber is a typical nonlinear material, and it has an obvious hysteresis characteristic [4,5]. It is a good damping material because of its vibration absorption performance.…”
Section: Introductionmentioning
confidence: 99%